Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1080/00016489.2017.1297538
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological survey of acute low-tone sensorineural hearing loss

Abstract: Objectives: A nationwide epidemiological survey involving 23 hospitals in Japan was conducted and the predictive values of demographic data were examined statistically. Methods: A total of 642 patients from 23 hospitals, including 20 university hospitals, in Japan were enrolled in the study. Age ranged from 8 to 87 years, and all were diagnosed with acute low-tone sensorineural hearing loss (ALHL) between 1994 and 2016. Demographic data for the patients, such as symptoms, gender, mean age, and distribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 8 publications
2
23
0
5
Order By: Relevance
“…With incidence as high as 65.8 per 100000 population, ALHL is recently receiving more attention regarding its epidemiology, treatment, and prognosis. 7) In this study, the demographic data showed marked female preponderance and peak incidence during fourth decade of life, which is comparable to demographic data in previous literature. 8) Of 249 patients who visited our clinic complaining of low-tone hearing loss and ear fullness without vertigo, approximately 20% met criteria for ALHL.…”
Section: Discussionsupporting
confidence: 90%
“…With incidence as high as 65.8 per 100000 population, ALHL is recently receiving more attention regarding its epidemiology, treatment, and prognosis. 7) In this study, the demographic data showed marked female preponderance and peak incidence during fourth decade of life, which is comparable to demographic data in previous literature. 8) Of 249 patients who visited our clinic complaining of low-tone hearing loss and ear fullness without vertigo, approximately 20% met criteria for ALHL.…”
Section: Discussionsupporting
confidence: 90%
“…Low-tone SSNHL differed from the sudden SSNHL in terms of male-to-female ratio, age distribution, pathology (ELH), treatment methods, and high hearing recovery prognosis. They thought that the two diseases belonged to different categories of inner ear disease [Shimono et al, 2013;Im et al, 2016;Sato et al, 2017;Yoshida et al, 2017;Myung et al, 2018;Psillas et al, 2019;Yakunina et al, 2019]. From our study, we speculate that history of migraine maybe another cause of low-tone SSNHL.…”
Section: Discussionmentioning
confidence: 47%
“…Most patients were simultaneously treated with vitamin B12 and adenosine triphosphate. The detailed treatments outcome of SSNHL and ALHL are described in other papers in this supplement [8][9][10].…”
Section: Gradementioning
confidence: 99%